Building capacity in health facility management: guiding principles for skills transfer in Liberia - Dahn Bernice T; Cleveland Emily; Brillant Sister; Rowe Laura A; Ramanadhan Shoba; Podesta Mae; Bradley Elizabeth H (BMC, 2010)
Abstract Background Management training is fundamental to developing human resources for health. Particularly as Liberia revives its health delivery system, facility and county health team managers are central to progress. Nevertheless, such management skills are rarely prioritized in health training, and sustained capacity building in this area is limited. We describe a health management delivery program in which a north and south institution collaborated to integrate classroom and field-based training in health management and to transfer the capacity for sustained management development in Liberia. Methods We developed and implemented a 6-month training program in health management skills (i.e. strategic problem solving, financial management, human resource management and leadership) delivered by Yale University and Mother Patern College from Liberia, with support from the Clinton HIV/AIDS Initiative. Over three 6-month cycles, responsibility for course instruction was transferred from the north institution to the south institution. A self-administered survey was conducted of all participants completing the course to measure changes in self-rated management skills, the degree to which the course was helpful and met its stated objectives, and faculty members' responsiveness to participant needs as the transfer process occurred. Results Respondents (n = 93, response rate 95.9%) reported substantial improvement in self-reported management skills, and rated the helpfulness of the course and the degree to which the course met its objectives highly. Levels of improvement and course ratings were similar over the three cohorts as the course was transferred to the south institution. We suggest a framework of five elements for implementing successful management training programs that can be transferred and sustained in resource-limited settings, including: 1) use a short-course format focusing on four key skill areas with practical tools; 2) include didactic training, on-site projects, and on-site mentoring; 3) collaborate with an in-country academic institution, willing and able to scale-up and maintain the training; 4) provide training for the in-country academic faculty; and 5) secure Ministry-level support to ensure participation. Conclusion Our findings demonstrate key elements for scaling up and replicating educational initiatives that address management skills essential for long-term health systems strengthening in resource-poor settings.